Territorial innovation, social ventures and local development: an exploratory case study - Bernardino, Susana (2016)
Social innovation is recognized as an important driver of growth and social value creation. Social innovative strategies are often pursued at the local level, by (social) organizations which have a more comprehensive knowledge of the complex social problems that a specific community is facing. The objective of the present study is to analyse the extent to which innovative social ventures are able to contribute to local development. By means of a qualitative approach, based on the case study method, we attempt to illustrate the innovative strategies conceived on the ground by a social venture specifically created to foster the local development of its inhabitants. The results shows that social innovation is a viable strategy to revitalize the economic growth of a region, through the creation of local employment on the basis of village’s traditional activities that are redefined in a new and competitive way. However, to be successful the strategy demands the deep knowledge of existing social problems as well as the availability of endogenous local resources and capabilities that could be used by social entrepreneurs. Therefore, social innovation ensures that local development and social cohesion are achieved in a sustainable way, at the same time that cultural and environmental heritage are also preserved.